Rights Not Rescue: Lessons from migrant domestic workers in the UK and their struggle for systems change - Roberts, Kate (Anti-Trafficking Review, 2020)
Response to the ATR debate proposition ‘It is worth undermining the anti-trafficking cause in order to more directly challenge the systems producing everyday abuses within the global economy.’